TEACHING SPEAKING SKILL IN THE ENGLISH LANGUAGE CLASSROOM - Sabina Nurmat qizi Janibekova; Nafisa Raimovna Kobilova (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Speaking is one of the four essential skills of the English language that must be taught to students, and one of the difficult fields to both teach and to learn. Speaking skill is the ability to communicate ideas, thoughts, and information in a clear, logical and engaging way. However, students often encounter certain difficulties during speaking. This article explains barriers that prevent junior high school students from developing their English speaking abilities, and identify the most effective strategies.